Mère et fils dans la cité démocratique des Athéniens - Claudine Leduc (Pallas, 2011)
The mother/son relationship is studied from a definite case in the demosthenian corpus, that of Plangon and her two sons. A “woman of no quality”, daughter, wife and mother of citizens who has only what she owes to her filiation : a name, a status and a rank. Her case, however, reveals the role which the democratic city and the proprietary “household” attribute to the mother in the designation of her sons as successors and heirs to their father.